Squamous cell carcinoma metastatic from uterus to mandible - Case report - Luciano Serpe; Ramon César Godoy Gonçalves; Roberto de Oliveira Jabur; Marcelo Carlos Bortoluzzi (Sociedade Portuguesa de Estomatologia e Medicina Dentária, 2022)
The present study is a case report of a possible case of metastasis of a squamous cell carcinoma from the uterus to the mandible. In this case, the patient had symptoms of volume increasing on the left side of the mandible some months after being diagnosed and treated for a squamous cell carcinoma in the uterus. The maxillofacial lesion reached the left mandibular angle region, which required surgical resection of the affected area and the installation of a 2.4-mm titanium plate system. Histopathological examination of the mandibular lesion pointed to squamous cell carcinoma. The patient died a few months after the procedure in the mandible due to complications of the primary tumor in the uterus. After an extensive literature review, no cases of metastatic squamous cell carcinoma from the uterus to the maxillofacial region were found, meaning this work may be the first case report in the literature.